2022
DOI: 10.3390/nano12020245
|View full text |Cite
|
Sign up to set email alerts
|

Facile Synthesis of Silane-Modified Mixed Metal Oxide as Catalyst in Transesterification Processes

Abstract: The fast depletion of fossil fuels has attracted researchers worldwide to explore alternative biofuels, such as biodiesel. In general, the production of biodiesel is carried out via transesterification processes of vegetable oil with the presence of a suitable catalyst. A mixed metal oxide has shown to be a very attractive heterogeneous catalyst with a high performance. Most of the mixed metal oxide is made by using the general wetness impregnation method. A simple route to synthesize silane-modified mixed met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 32 publications
1
3
0
Order By: Relevance
“…The FT-IR spectrum of CaO and 10% Co/CaO is shown in Figure . The peak at 3634 cm –1 showed that in both cases (CaO and Co/CaO), higher stretching vibration of O–H was present on the surface of the catalysts due to the basic nature of CaO catalysts to adsorb H 2 O . The stretching vibrational peak at 866 and 1443 cm –1 indicated that catalysts adsorb CO 2 from the atmosphere and form carbonate during the storage and preparation processes, which was also confirmed from XPS results (Figure ).…”
Section: Resultssupporting
confidence: 66%
See 1 more Smart Citation
“…The FT-IR spectrum of CaO and 10% Co/CaO is shown in Figure . The peak at 3634 cm –1 showed that in both cases (CaO and Co/CaO), higher stretching vibration of O–H was present on the surface of the catalysts due to the basic nature of CaO catalysts to adsorb H 2 O . The stretching vibrational peak at 866 and 1443 cm –1 indicated that catalysts adsorb CO 2 from the atmosphere and form carbonate during the storage and preparation processes, which was also confirmed from XPS results (Figure ).…”
Section: Resultssupporting
confidence: 66%
“…The peak at 3634 cm −1 showed that in both cases (CaO and Co/CaO), higher stretching vibration of O−H was present on the surface of the catalysts due to the basic nature of CaO catalysts to adsorb H 2 O. 26 The stretching vibrational peak at 866 and 1443 cm −1 indicated that catalysts adsorb CO 2 from the atmosphere and form carbonate during the storage and preparation processes, 26 which was also confirmed from XPS results (Figure 6). After the addition of cobalt metal, some new peaks at 730, 530, and 470 cm −1 were formed as the catalysts possessed Ca−O and Co−O in the form CaCoO metal oxide.…”
Section: Resultsmentioning
confidence: 96%
“…With increasing energy demand, the consumption of fossil fuels, and their negative impact on the environment, such as environmental pollution, global warming, and rising sea levels, great attention has been given to researching renewable and clean biofuels. [1][2][3][4] Biodiesel, a green, biodegradable, renewable and sustainable biofuel, is usually made from waste vegetable oils and animal fats. The composition of biodiesel is alkyl esters of fatty acids derived from vegetable oils and fats.…”
Section: Introductionmentioning
confidence: 99%
“…Colloidal methods are widely used for the fabrication of advanced nanomaterials and nanocomposites [ 1 , 2 , 3 ]. The use of surfactants for colloidal nanofabrication allows efficient control of particle size and prevention of their agglomeration [ 4 , 5 , 6 , 7 ]. Of particular interest is the use of surfactants for the fabrication of nanocomposite electrodes for energy storage in supercapacitors.…”
Section: Introductionmentioning
confidence: 99%